Volume reconstruction of large tissue specimens from serial physical sections using confocal microscopy and correction of cutting deformations by elastic registration - Capek, Martin; Brůza, Petr; Janácek, Jirí; Karen, Petr; Kubínová, Lucie; Vagnerová, Radomíra (Microscopy research and technique, 2009)
A set of methods leading to volume reconstruction of biological specimens larger than the field of view of a confocal laser scanning microscope (CLSM) is presented. Large tissue specimens are cut into thin physical slices and volume data sets are captured from all studied physical slices by CLSM. Overlapping spatial tiles of the same physical slice are stitched in horizontal direction. Image volumes of successive physical slices are linked in axial direction by applying an elastic registration algorithm to compensate for deformations because of cutting the specimen. We present a method enabling us to keep true object morphology using a priori information about the shape and size of the specimen, available from images of the cutting planes captured by a USB light microscope immediately before cutting the specimen by a microtome. The errors introduced by elastic registration are evaluated using a stereological point counting method and the Procrustes distance. Finally, the images are enhanced to compensate for the effect of the light attenuation with depth and visualized by a hardware accelerated volume rendering. Algorithmic steps of the reconstruction, namely elastic registration, object morphology preservation, image enhancement, and volume visualization, are implemented in a new Rapid3D software package. Because confocal microscopes get more and more frequently used in scientific laboratories, the described volume reconstruction may become an easy-to-apply tool to study large biological objects, tissues, and organs in histology, embryology, evolution biology, and developmental biology. In this work, we demonstrate the reconstruction using a postcranial part of a 17-day-old laboratory Wistar rat embryo.
Keywords: Imaging, Three-Dimensional; embryo savčí; pružnost; Image Processing, Computer-Assisted; Elasticity; Microscopy, Confocal; Microtomy; algoritmy; Rats; zvířata; Algorithms; zobrazování trojrozměrné; Embryo, Mammalian; krysa rodu Rattus; konfokální mikroskopie; počítačové zpracování obrazu; mikrotomie; Animals